Implementation of the Supervisory Function of Customs Office Type Madya Pabean B Sidoarjo in Addressing the Distribution of Illegal Cigarettes in Sidoarjo Regency - Rishad Daristama Baihaqi; Bima Ferronsyah; Lidia Patricia Manullang; Dhea Hilda Maharani; Ertien Rining Nawangsari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study aims to analyze the implementation of the supervisory function by the Customs and Excise Supervision and Services Office (KPPBC) Type Madya Pabean B Sidoarjo in addressing the circulation of illegal cigarettes in Sidoarjo Regency. The research employs a qualitative approach with data collection techniques including interviews, observation, and document study. The results indicate that KPPBC TMP B Sidoarjo applies two main approaches: direct supervision (through field inspections, observations, and real-time reports) and indirect supervision (based on written and verbal reports from the public and related agencies). Supporting factors include inter-agency collaboration and community participation, while the main obstacles consist of incomplete reporting and social resistance. The study concludes that the supervision strategy has successfully limited the mobility of illegal actors, although it has not entirely eliminated such activities. Recommendations include enhancing public education, optimizing technology, and adjusting policies to strengthen supervisory effectiveness. These findings contribute to the development of more adaptive and integrated illegal cigarette surveillance strategies. Keywords: Customs Supervision, Direct Supervision, Indirect Supervision, Illegal Cigarettes, Sidoarjo Regency.